Proceedings of the 32nd ACM/IEEE International Conference on Software Engineering - Volume 1 2010
DOI: 10.1145/1806799.1806855
|View full text |Cite
|
Sign up to set email alerts
|

Linking e-mails and source code artifacts

Abstract: E-mails concerning the development issues of a system constitute an important source of information about high-level design decisions, low-level implementation concerns, and the social structure of developers.Establishing links between e-mails and the software artifacts they discuss is a non-trivial problem, due to the inherently informal nature of human communication. Different approaches can be brought into play to tackle this traceability issue, but the question of how they can be evaluated remains unaddres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(117 citation statements)
references
References 23 publications
0
115
0
2
Order By: Relevance
“…Once the model is generated, the parsing infrastructure classifies the content of the documentation and the support channel: it identifies the codelike terms, the code snippets, and their probable kind (e.g., class, method, XML element, Java code snippet, XML code snippet). We relied on existing techniques described in the literature [7] and in our previous work [12] to implement the content classification step. A brief description of the classification process and the evaluation of its accuracy is presented in a technical report [13].…”
Section: Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once the model is generated, the parsing infrastructure classifies the content of the documentation and the support channel: it identifies the codelike terms, the code snippets, and their probable kind (e.g., class, method, XML element, Java code snippet, XML code snippet). We relied on existing techniques described in the literature [7] and in our previous work [12] to implement the content classification step. A brief description of the classification process and the evaluation of its accuracy is presented in a technical report [13].…”
Section: Sectionmentioning
confidence: 99%
“…Bacchelli et al compared various techniques to identify code elements and code snippets in email messages and found that lightweight techniques based on regular expressions performed better than information retrieval techniques such as latent semantic indexing [7]. We implemented our documentation and support channel parsers with regular expressions based on the observations of this study.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Trace the related artifacts that contain the external links as prepared by bacchelli al. [8] to identify all the mail messages defined. …”
Section: Mining Unstructured Data In Software Repositories: Current Amentioning
confidence: 99%
“…For example, Bachelli et al [21], [22] investigated the interlinking of email data from mailing lists with commit or patch data. The area of traceability research (e.g., [23], [24]) addresses the interlinking of source code changes with documentation changes.…”
Section: Related Workmentioning
confidence: 99%